2021
DOI: 10.1590/1516-4446-2020-0945
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Morinda officinalis oligosaccharide capsules for depressive disorder: a systematic review and meta-analysis

Abstract: To evaluate the efficacy and safety of Morinda officinalis oligosaccharide (MOO) capsules for depressive disorder. Methods: Eight electronic databases were searched for relevant studies from inception to April 19, 2020. Randomized controlled trials comparing MOO capsules with antidepressants were included. Data analysis was conducted using Review Manager 5.3 software. The risk of bias was assessed using the Cochrane Risk of Bias Tool, and the quality of the studies was evaluated by two researchers using the Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…MOO, a mixture of oligosaccharides ranging from trisaccharides to nonasaccharides and mainly consisting of seven oligosaccharides 12 , have shown pharmacological activities on anti-depressant, anti-dementia and memory-enhancing effects 13 , 14 . MOO has been approved to be a prescription drug against depressant in China in 2012 15 (NMPA approval number: Z20120013), making them a clinical traditional Chinese medicine (TCM) for the treatment of depression. The results of Phase I clinical trial in China 16 showed that after taking MOO capsules, all healthy volunteers in the study showed good tolerance, in groups either administered with MOO as a single dose (50–1000 mg) or continuously administration for 7 days (800 mg/day).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOO, a mixture of oligosaccharides ranging from trisaccharides to nonasaccharides and mainly consisting of seven oligosaccharides 12 , have shown pharmacological activities on anti-depressant, anti-dementia and memory-enhancing effects 13 , 14 . MOO has been approved to be a prescription drug against depressant in China in 2012 15 (NMPA approval number: Z20120013), making them a clinical traditional Chinese medicine (TCM) for the treatment of depression. The results of Phase I clinical trial in China 16 showed that after taking MOO capsules, all healthy volunteers in the study showed good tolerance, in groups either administered with MOO as a single dose (50–1000 mg) or continuously administration for 7 days (800 mg/day).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism studies for MOO have demonstrated some of its activities in brain, such as enhancing 5-HT neurotransmission, increasing the expression of neurotrophic factor and changing glucose metabolism 19 , 20 . A clinical study showed a significant therapeutic efficacy of MOO capsules in 1384 individuals with mild to moderate depression, and the improvement was not less than that of conventional antidepressants such as fluoxetine hydrochloride and escitalopram 15 . However, based on previous studies, MOO had poor absorption in oral administration 21 ; thus MOO's concentration in blood or brain might be very low.…”
Section: Introductionmentioning
confidence: 99%
“…officinalis oligosaccharides, MOO), have exhibited significant pharmacological activities including anti-depressant, anti-dementia, and memory enhancement . Capsules of MOO mixtures have been approved in China as an oral prescribed drug for treating mild and moderate depression since 2012 …”
Section: Introductionmentioning
confidence: 99%
“…7 Capsules of MOO mixtures have been approved in China as an oral prescribed drug for treating mild and moderate depression since 2012. 8 Recent research has unraveled the correlation of MOO's antidepressant effects with the microbiota−gut−brain axis by regulating 5-HT synthesis in the gut microbiota. 9 More importantly, in-depth studies on every single component in MOO indicated that pentasaccharide exerted a significant antidepressant effect through the mechanism identical to that of the MOO mixture and may be the main anti-depressant constituent in MOO.…”
Section: ■ Introductionmentioning
confidence: 99%